PROCEDURES OF STATE REGISTRATION AND CERTIFICATION OF CIVIL AERODROMES IN THE CONTEXT OF UKRAINE’S OBLIGATIONS UNDER THE CONVENTION ON INTERNATIONAL CIVIL AVIATION - Rozum, Igor O.; Trotsyuk, Nina V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: within the framework of the scientific article, the group of authors thoroughly analyzed the administrative and legal principles of the organization of state registration and certification of airfields of civil aviation in the context of Ukraine's international obligations under the Convention on International Civil Aviation and its Annexes. Methods: methodological basis of the study consisted of both general scientific and special-legal methods of scientific knowledge. The application of the logical-semantic method in combination with the formal-legal one allowed to highlight and define the essence and content of the procedures for state registration of certification in the aspect of aviation activity related to the operation of civil aviation airfields by subjects of relevant public legal relations. The application of the analysis method in combination with the formal legal method enabled the legal basis for the procedures for registration and certification of aerodromes of civil aviation to be worked out, as well as to study the peculiarities of the legal status of subjects of power and management powers in the process of their implementation. The grouping method allowed systematizing the stages and procedural phases of registration and certification procedures. By means of the synthesis method in combination with rather-legal (comparative) and formally-legal methods were generalized international standards and recommended practices of ICAO for the construction, commissioning, reconstruction of airfields of civil aviation, carrying out repair, technological or other types of works within their framework. Discussion: the administrative and legal aspects of the procedures for state registration and certification of civil aviation airfields remain the subject of purely scientific developments, which enables full comprehension of their content and legal nature. The raised issues acquire particular topicality in the context of the need for proper implementation of Ukraine's international obligations to ensure aviation safety, regularity and efficiency of flights by introducing rules, practices and procedures that provide for measures to protect against acts of unlawful interference.